Arrangements and populations of beans in a mixed cropping with maize - Reis, Wagner Pereira; Ramalho, Magno Antonio Patto; Cruz, José Carlos (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments were carried out at Sete Lagoas and Lavras, state of Minas Gerais, Brazil, during the growing season of 1982/83, in order to evaluate new planting patterns for intercropping of maize and beans. The evaluated treatments involved three maize row spacings (0.5 m, 1 m and 1.5 m), for a constant population of 40,000 plants/ha, combined with two bean populations (100,000 and 200,000 plants/ha) with three planting systems: within the rows, between the rows and both between the rows of maize. The results showed that the increment of row spacing of the maize had no effect on the grain yield of the intercropping. There was no significant effect between the systems of planting beans. This results showed once more, that planting beans within the maize rows is more advantageous due to the management facilities it provides. The highest bean plant density contributed for better productivity, and there was no effect on the grain yield maize. The competition effect reduced the grain yield of beans in 39% and the pod number was the most affected primary component of grain production, because of the reduction of the number of flowers, although the yield from the floral stage was also affected.
Keywords: phaseolus vulgaris; zea mays; legumes